Applicability of the Tanaka–Johnston and Moyers mixed dentition analyses in Northeast Han Chinese. (June 2015) - Sherpa, Jangbu; Sah, Gopal; Rong, Zeng; Wu, Lipeng
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives: To assess applicability of the Tanaka–Johnston and Moyers prediction methods in a Han ethnic group from Northeast China and to develop prediction equations for this same population. Design: Cross-sectional study. Setting: Department of Orthodontics, School of Stomatology, Jiamusi University, Heilongjiang, China. Participants: A total of 130 subjects (65 male and 65 female) aged 16–21 years from a Han ethnic group of Northeast China were recruited from dental students and patients seeking orthodontic treatment. Ethnicity was verified by questionnaire. Material and methods: Mesio-distal tooth width was measured using Digital Vernier calipers. Predicted values were obtained from the Tanaka–Johnston and Moyers methods in both arches were compared with the actual measured widths. Based on regression analysis, prediction equations were developed. Results: Tanaka–Johnston equations were not precise, except for the upper arch in males. However, the Moyers 85th percentile in the upper arch and 75th percentile in the lower arch predicted the sum precisely in males. For females, the Moyers 75th percentile predicted the sum precisely for the upper arch, but none of the Moyers percentiles predicted in the lower arch. Conclusions: Both the Tanaka–Johnston and Moyers method may not be applied universally without question. Hence, it may be safer to develop regression equations for specific populations. Validating studies must be conducted to confirm the precision of these newly developed regression equations.